Definición de estrategias de transformación de la cultura organizacional en función de un sistema de gestión de calidad (2009)
This article presents a conceptual and methodological proposal for managing the integration of the principles and characteristics of a quality management system based on the standard ISO 9000 and 9001 in the organizational culture, within the framework of its implementation, in order to promote the successful operation and sustainability of the System. It includes proposals to: diagnose the culture, change management methodology, and strategies to incorporate quality principles into the organizational culture. It is based on analysis and relationship between the concepts of organizational culture, quality culture and cultural aspects identified in the ISO Standard